Tiga Tema Konsep Kebersyukuran dalam Perspektif Al-Qur’an: Sebuah Literatur Review - Karimulloh (Jurnal Studi Al-Qur'an, 2021)
Abstract A human being receives many blessings, but a few people who are considered as grateful human in the Qur'an are important things to study. There are few studies discussing gratefullness (shukr) in Indonesia. Mostly talking gratitude from social and individual perspectivem but lack of Islamic literacy, especially from the primary Islamic reference source, namely the Al-Qur'an, is the main objective of this research. The research method used is literature review study by analyzing the verses of gratitude in the Al-Qur'an with a thematic interpretation approach and Islamic science studies. The results of the study show that there are three major themes of the concept of gratitude contained in the Qur'an and supported by the interpretations of the scholars. The three major themes are (1). The command to be grateful in the perspective of the Al Quran, (2) the positive impact of gratitude contained in the Al Quran, and (3) the factors that cause gratitude described in the Al Quran. This result also explains that a grateful person must get the pleasure of Allah SWT, and he will avoid the torment of hellfire and get additional favours, both in this world and in the hereafter. So that someone can be grateful, it is advisable to look at people who are lower in rank, remember the blessings that Allah has given him, and ask Allah SWT to be given the strength to give thanks to Him.